High-throughput sequencing data of the microbiota and antibiotic resistance genes from biofilms on polystyrene and nylon rope incubated in Bergen harborNCBI SRA - Didrik H. Grevskott; Manish P. Victor; Tyra E. Lima; Vera Radisic; Priyank S. Nimje; Nachiket P. Marathe (Data in Brief)
Plastics can provide a hydrophobic surface for microorganisms to attach, colonize and form microbial biofilms, referred to as ‘plastisphere.’ The aim of this study was to determine the microbiota of biofilms on plastic, using field trials in Bergen harbour, Norway using metagenomics. Polystyrene (PS) and nylon ropes (PA) were submerged in sea for four weeks, biofilm communities were collected, and the extracted DNA was subjected to metagenomic sequencing (n=12). The average salinity and temperature during the experiment were 9.02 °C (8.2-10.7) and 28.85 ‰ (26.1 ‰ - 33.1 ‰). We obtained a total of ∼460 Gigabases of sequence data from our samples. Gammaproteobacteria and Alpha proteobacteria were the most prominent on these polymers with β-lactamases as the most abundant resistance gene class. The datasets will be useful for the scientific community working on plastic-associated biofilms.